2022
DOI: 10.1007/s10750-022-04873-1
|View full text |Cite
|
Sign up to set email alerts
|

Size matters: variations in seagrass seed size at local scales affects seed performance

Abstract: Seed size can have an impact on angiosperm reproductive fitness. Ecological theory predicts plants that will produce larger seeds in stressful environments to increase the chances of seedling survival and numerous small seeds in favourable conditions to increase the number of recruits. We measured seed morphology of the seagrass Heterozostera nigricaulis from four populations under differing environmental conditions in South East Australia. Seed size and mass among sites showed consistent differences over four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 76 publications
1
2
0
Order By: Relevance
“…These discrepancies could be attributed to variations in experimental conditions that influence germination behavior. Consistent with previous studies [ 47 , 48 ], our results demonstrated that seedlings derived from heavier seeds had greater biomass than those derived from lighter seeds, likely due to the presence of greater seed reserves in their cotyledons [ 49 , 50 ]. Intuitively, heavier seeds would seem to be advantageous because seed mineral reserves should increase as a function of total seed mass [ 51 , 52 ].…”
Section: Discussionsupporting
confidence: 92%
“…These discrepancies could be attributed to variations in experimental conditions that influence germination behavior. Consistent with previous studies [ 47 , 48 ], our results demonstrated that seedlings derived from heavier seeds had greater biomass than those derived from lighter seeds, likely due to the presence of greater seed reserves in their cotyledons [ 49 , 50 ]. Intuitively, heavier seeds would seem to be advantageous because seed mineral reserves should increase as a function of total seed mass [ 51 , 52 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, this was only observed at one of our study locations (Jack's Beach), with overall germination rates too low at Corinella to detect any differences effectively. Nonetheless, seed quality is still likely to be important, with previous studies showing, for example, that larger seeds of Heterozostera nigricaulis had higher germination success and remained viable longer than smaller seeds of the same species (Smith et al 2022). Like seed viability, seed quality should also be further explored to improve germination success.…”
Section: Discussionmentioning
confidence: 99%
“…de Jager et al (2019) reveal that in warm lowlands, large seeds generally spread more widely than small seeds when carried by flowing water. Besides that, large seeds that come from open-growth environments will be more adaptable than small seeds (Smith et al 2022). Small seeds are preferred by rodents as dispersal agent in the zoochory mechanism (Lang & Wang 2016).…”
mentioning
confidence: 99%